(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Identity is often described as finite and consists of separate and distinct parts such as; family, culture, personal relations and profession, to name a few. The formation of identity is an ever – evolving one wherein our genealogy, culture, loved ones, those we cared for, people who have harmed us and people we have harmed, our memories of the various phases of life, or the deeds done to oneself and to others, experiences lived and choices made, all come together to form who one is, at a given moment. The black Americans in the select novels are neglected even not to be considered as human beings, deprived of their rights. This article deals with the search for self as to who they truly are in the novel of Toni Morrison’s Beloved and The Bluest Eye. Identity is the uniqueness of a person and when it is lost, the person loses everything in his life.